Circulating Tumor-Cell-Associated White Blood Cell Clusters in Peripheral Blood Indicate Poor Prognosis in Patients With Hepatocellular Carcinoma - Luo, Qiong; Wang, Chunming; Peng, Bangjian; Pu, Xiaoyu; Cai, Lei; Liao, Hangyu; Chen, Kunling; Zhang, Cheng; Cheng, Yuan; Pan, Mingxin (Frontiers in Oncology, 2020)
Aim Circulating tumor cells (CTC) are a precursor to metastasis in several types of cancer and are occasionally found in the bloodstream in association with immune cells, such as white blood cells (WBCs). CTC-associated WBC (CTC-WBC) clusters can promote CTC appreciation and metastasis, suggesting that patients with CTC-WBC clusters found in the peripheral blood may have a worse prognosis. However, it is unclear whether CTC-WBC clusters are present in the peripheral blood of patients with hepatocellular carcinoma (HCC) and suggest a poor prognosis for HCC. Methods We collected peripheral blood from 214 patients with HCC from January 2014 to December 2016. CanPatrolTM CTC analysis technology was used to isolate and count CTCs and CTC-WBC clusters in the patients’ peripheral blood. Chi-squared analysis was used to calculate the correlation between the CTC-WBC clusters and clinicopathological characteristics. Kaplan–Meier survival analysis and Cox regression analysis were used to assess patient prognosis. Results We used CanPatrolTM CTC analysis technology to count different types of CTCs and CTC-WBC clusters. The results showed that CTC-WBC clusters and tumor size(P=0.001), tumor number(P=0.005), portal vein tumor thrombus (P=0.026), BCLC stage (P＜0.001), AFP level (P=0.002), and total number of CTCs(P＜0.001) were statistically related. Cox regression analysis revealed that CTC-WBC clusters are an independent prognostic indicator of DFS (HR=1.951, 95%CI:1.348-2.824, P＜0.001) and OS (HR=3.026, 95%CI:1.906-4.802, P＜0.001) in HCC patients. Using Kaplan–Meier analysis, we found that positive CTC-WBC cluster patients had significantly shorter DFS and OS than patients with negative CTC-WBC (P＜0.001 and P＜0.001, respectively). Conclusions CTC-WBC clusters in the peripheral blood are an independent predictor of DFS and OS, and their presence indicates poor prognosis in patients with HCC.